Zirconium oxide coated potassium doped lithium zinc titanate negative electrode material and preparation method thereof
By coating zirconia with potassium doped zinc titanate material, the problem of insufficient conductivity of zinc titanate lithium material is solved, and better electrochemical performance is achieved, including the improvement of cycle stability and rate performance.
Patent Information
- Application Number
- CN202211014952.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-23
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-08-23
AI Technical Summary
In the prior art, the electronic conductivity of zinc titanate lithium material is poor, which limits its application in lithium-ion batteries. Although the existing doping and coating methods improve electrochemical performance, the improvement is limited.
Zirconia coated with potassium doped zinc titanate material, and zirconium oxide coating is prepared by potassium chloride doping, zirconium acetate and citric acid to improve the electronic conductivity and ionic conductivity of the material, and to ensure crystallization with microwave sintering technology Particle homogeneity.
The electrochemical performance of zinc titanate lithium material is significantly improved, including enhanced cycling stability, rate performance and reduced charge transfer impedance, optimize the transmission channel of lithium ions, and improve the overall conductivity of the material.
Smart Images

Figure CN115241442B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode materials for lithium ion batteries, and in particular relates to a zirconium oxide-coated potassium-doped lithium zinc titanate negative electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries have the advantages of high specific energy, small size, long cycle life, and high operating voltage, and have been widely used. As one of the important components of lithium-ion batteries, the negative electrode material will directly affect the electrochemical performance of the battery. 2 ZnTi 3 O 8 (LZTO) has the advantages of non-toxicity, good safety, low cost, relatively high theoretical and low discharge voltage platform (about 0.5 V (vs. Li / Li + )) has received much attention. However, due to the poor electronic conductivity of LZTO, its practical application is limited. Therefore, it is particularly important to find a way to make LZTO have good electrical conductivity and ionic conductivity.
[0003] At present, in order to overcome these defects, commonly used methods such as carbon coating, improved preparation process, ion doping, etc. Carbon materials have the advantages of low price, high natural abundance, good conductivity, small dosage required for modification, stable physical and chemical properties, etc., which can not only obtain high conductivity of the matrix material, but also reduce the side reaction between the electrode material and the electrolyte. Therefore, carbon coating is considered to be a convenient modification method to improve the conductivity of electrode materials. Structural nano-sizing can increase the surface area of the material, which is conducive to the full penetration of the electrode material and the electrolyte. Doping ions can improve the ionic conductivity and electronic conductivity of LZTO. The doping position and doping amount will affect the electrochemical properties of the electrode material.
[0004] For example, the literature (Zeng XG, et al. Frontiers in Chemistry, 2021, 8: 1-7) in Li 2 ZnTi 3 O 8 Add Cr(NO 3 ) 3 , Cr is achieved by liquid phase method 3+ The experimental results show that at a current density of 2 Ag −1 and 5 A g −1 When Li 2 ZnTi 2.9 Cr 0.1 O 8 The discharge capacity is 156.7 mAh g -1and 107.5 mAh g −1 In addition, even at a current density of 1 A g −1 In the case of 200 cycles, the reversible specific capacity is still maintained at 162.2 mAhg −1 It can be seen that Cr 3+ The doping of Li 2 ZnTi 2.9 Cr 0.1 O 8 conductivity, thereby improving its electrochemical performance.
[0005] There is also a literature (Li Y., et al. Ceramics International, 2021, 47(13):18732-18742) that uses a simple hydrothermal method to prepare Li 2 ZnTi 3 O 8 @α-Fe 2 O 3 Composite materials. 2 ZnTi 3 O 8 / α-Fe 2 O 3 The composite material showed 2 ZnTi 3 O 8 Similar irregular spherical morphology, and similar to the original Li 2 ZnTi 3 O 8 The particle size is relatively small. 2 ZnTi 3 O 8 / α-Fe 2 O 3 In the composite material, Li 2 ZnTi 3 O 8 / α-Fe 2 O 3 The composite material (5 wt.%) has the best electrochemical performance. Li 2 ZnTi 3 O 8 / α-Fe 2 O 3 Composite material (5 wt.%) at 1000 mA g −1 The reversible charge capacity after 500 cycles is 184.8 mAh g −1 , while the original Li 2 ZnTi 3 O 8Only offers 110.7 mAh g -1 Reversible charge capacity. Li 2 ZnTi 3 O 8 With α-Fe 2 O 3 The formation of strong covalent bonds between them is beneficial to reduce the interfacial energy and stabilize the composite material. Due to the special synergistic effect of the multiphase interface, Li 2 ZnTi 3 O 8 / α-Fe 2 O 3 The composite materials not only possess the advantages of single components but also exhibit novel and attractive properties such as enhanced ionic conductivity, reduced interfacial charge transfer impedance, improved lithium ion mobility, and enhanced rate capability and reversible capacity.
[0006] Although both doping and coating improve the electrochemical performance, the electrochemical performance of the negative electrode materials currently prepared is limited. Therefore, how to further improve the electrochemical performance of lithium zinc titanate is a technical problem that those skilled in the art hope to solve. Summary of the invention
[0007] In view of the above-mentioned deficiencies in the prior art, the purpose of the present invention is to provide a zirconium oxide-coated potassium-doped lithium zinc titanate negative electrode material and a preparation method thereof. The negative electrode material obtained by the preparation method has good electronic conductivity and ionic conductivity and has good electrochemical properties.
[0008] The technical solution of the present invention is achieved in this way:
[0009] A method for preparing a zirconium oxide coated potassium doped lithium zinc titanate negative electrode material, wherein the zirconium oxide coated potassium doped lithium zinc titanate negative electrode material has the general chemical formula: Li x K y ZnTi 3 O 8 @ZrO 2 , wherein x+y=2, 0<y<0.2, and the preparation method thereof comprises the following steps:
[0010] S1: weigh anhydrous lithium acetate, zinc acetate dihydrate, nano titanium dioxide and potassium chloride according to the stoichiometric ratio, and then dissolve them in anhydrous ethanol and mix them evenly to obtain a mixed solution A for standby use;
[0011] S2: Heat and stir the mixed solution A, then dry and sinter to obtain Li x K y ZnTi 3 O 8 powder;
[0012] S3: Li x K y ZnTi 3 O 8 The powder is dissolved in deionized water and mixed evenly to obtain a mixed solution B for later use;
[0013] S4: preparing a solution of zirconium acetate and citric acid, and then adding the solution dropwise to the mixed solution B and stirring evenly to obtain a mixed solution C for later use;
[0014] S5: Place the mixed solution C in a sealed container and evaporate the solvent to obtain a white gel-like substance, then dry and sinter to obtain the Li x K y ZnTi 3 O 8 @ZrO 2 .
[0015] Furthermore, y=0.1.
[0016] Furthermore, in step S1, anhydrous lithium acetate, zinc acetate dihydrate and potassium chloride are first dissolved in anhydrous ethanol, ultrasonicated for 30-40 min, and then nano titanium dioxide is added and ultrasonicated for 30-40 min to obtain a mixed solution A.
[0017] Furthermore, in step S2, the mixed solution A is heated and stirred at a temperature of 75-85° C., and a gel-like substance is obtained after the solvent evaporates.
[0018] Further, the gel-like substance obtained in step S2 is placed in an oven at 75-85°C and dried to obtain a white powder, and then the white powder is placed in a microwave sintering furnace and sintered at 700-750°C for 15-20 min under an argon atmosphere to obtain Li x K y ZnTi 3 O 8 powder.
[0019] Furthermore, the molar ratio of zirconium acetate to citric acid is 1:1.
[0020] Further, in step S3, Li x K y ZnTi 3 O 8 The mass volume ratio of powder and deionized water is 3-8 g: 200-250 mL; in step S4, the mass of zirconium acetate is Li x K y ZnTi 3 O 8 1~5% of powder mass.
[0021] Furthermore, in step S5, the mixed solution C is placed in a sealed container and reacted at 75-80° C. for 2-3 h to obtain a white gel-like substance.
[0022] Further, in step S5, the white gel-like substance is dried at 75-85 °C for 24-36 h, and then placed in a muffle furnace and sintered at 400-450 °C for 5-6 h to obtain Li x K y ZnTi 3 O 8 @ZrO 2 .
[0023] The present invention also provides a zirconium oxide-coated potassium-doped lithium zinc titanate negative electrode material, which is prepared by the above-mentioned preparation method.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. The present invention first uses potassium chloride as a potassium source for doping and then coats lithium zinc titanate with zirconium oxide. The radius of potassium ions is larger than that of lithium ions. The addition of potassium ions can make Li x K y ZnTi 3 O 8 The lattice constant of the powder increases, so that x K y ZnTi 3 O 8 Defects are formed in the structure, and the formation of defects is beneficial to improve the activity of the material and broaden the transmission channel of lithium ions. Then zirconium acetate and citric acid solution are used to x K y ZnTi 3 O 8 A zirconium oxide coating layer is prepared on the surface of the powder. The zirconium oxide coating layer can effectively prevent the side reaction between lithium zinc titanate and the electrolyte. At the same time, zirconium oxide can effectively control the size of the material and shorten the transmission distance of lithium ions, thereby effectively improving the electronic conductivity and ionic conductivity of the material, thereby improving the electrochemical properties of lithium zinc titanate.
[0026] 2. The present invention adopts microwave sintering method to prepare Li x K y ZnTi 3 O 8 The powder can be heated from both inside and outside to make the prepared Li x K y ZnTi 3 O 8 The powder grains are more uniform, thus ensuring the Li x K yZnTi 3 O 8 @ZrO 2 uniformity, and also helps to shorten the reaction time.
[0027] 3. The present invention uses zirconium acetate and citric acid as raw materials to prepare the zirconium oxide coating layer. Citric acid and zirconium acetate are dissolved in deionized water respectively and then mixed with Li x K y ZnTi 3 O 8 Mixing can effectively ensure that zirconium acetate is evenly coated on the Li x K y ZnTi 3 O 8 surface, thereby ensuring that zirconium oxide formed by the decomposition of zirconium acetate is x K y ZnTi 3 O 8 A uniform zirconium oxide coating is formed on the surface. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 - Li prepared in Example 2 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 XRD patterns of the materials.
[0029] Figure 2 - Li prepared in Example 2 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 HRTEM image of the material.
[0030] Figure 3 -Li 2 ZnTi 3 O 8 And the Li prepared in Example 2 1.9 K 0.1 ZnTi 3 O 8 and Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 , Li prepared in Example 4 1.85 K 0.15 ZnTi 3 O 8 and Li prepared in Example 6 2 ZnTi 3 O8 @ZrO 2 Cycling performance diagram at a current density of 200 mA / g.
[0031] Figure 4 -Li 2 ZnTi 3 O 8 And the Li prepared in Example 2 1.9 K 0.1 ZnTi 3 O 8 and Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 , Li prepared in Example 4 1.85 K 0.15 ZnTi 3 O 8 and Li prepared in Example 6 2 ZnTi 3 O 8 @ZrO 2 Rate performance diagram.
[0032] Figure 5 -Li 2 ZnTi 3 O 8 And the Li prepared in Example 2 1.9 K 0.1 ZnTi 3 O 8 and Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 , Li prepared in Example 4 1.85 K 0.15 ZnTi 3 O 8 and Li prepared in Example 6 2 ZnTi 3 O 8 @ZrO 2 Impedance diagram.
[0033] Figure 6 -Li 2 ZnTi 3 O 8 And the Li prepared in Example 2 1.9 K 0.1 ZnTi 3 O 8 and Li 1.9 K 0.1ZnTi 3 O 8 @ZrO 2 Cyclic voltammogram of . DETAILED DESCRIPTION
[0034] The present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0035] Example 1
[0036] S1: Weigh 2.5076 g of anhydrous lithium acetate, 4.3900 g of zinc acetate dihydrate and 0.1491 g of potassium chloride and dissolve them in 250 ml of anhydrous ethanol. Ultrasonicate for 30 min. Then weigh 4.7922 g of nano titanium dioxide and add it to the above solution. Ultrasonicate for 30 min to obtain a mixed solution A.
[0037] S2: The mixed solution A was heated and stirred at 80 °C until the solvent evaporated to obtain a gel-like substance, which was then dried in an oven at 80 °C for 24 h; and then sintered in a microwave sintering furnace at 750 °C for 15 min in an argon atmosphere to obtain Li 1.9 K 0.1 ZnTi 3 O 8 powder;
[0038] S3: weigh 0.6 g Li 1.9 K 0.1 ZnTi 3 O 8 The powder was dissolved in 250 mL of deionized water and mixed evenly to obtain a mixed solution B;
[0039] S4: weigh 0.006 g of zirconium acetate and 0.00352 g of citric acid, dissolve the zirconium acetate in citric acid to prepare a solution, then add the solution dropwise to the mixed solution B, and stir to obtain a mixed solution C;
[0040] S5: The mixed solution C was reacted at 80 °C for 3 h in a sealed container, the solvent was evaporated, and then dried at 80 °C for 24 h and sintered in a muffle furnace at 400 °C for 5 h to obtain Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 .
[0041] Example 2
[0042] This example is the same as Example 1, except that the amount of zirconium acetate in this example is 0.018 g.
[0043] Example 3
[0044] This example is the same as Example 1, except that the amount of zirconium acetate in this example is 0.030 g.
[0045] Example 4
[0046] This embodiment is the same as Embodiment 2, except that, in this embodiment, the amount of anhydrous lithium acetate is 2.44163 g, the amount of zinc acetate dihydrate is 4.3900 g, the amount of potassium chloride is 0.22365 g, and the amount of nano-titanium dioxide is 4.7922 g.
[0047] Example 5
[0048] This example is the same as Example 2, except that in this example, the anhydrous lithium acetate is 2.57361 g, the zinc acetate dihydrate is 4.3900 g, the potassium chloride is 0.07455 g, and the nano titanium dioxide is 4.7922 g.
[0049] Example 6
[0050] This example is the same as Example 2, except that in this example, the anhydrous lithium acetate is 2.6396 g, the zinc acetate dihydrate is 4.3900 g, the nano-titanium dioxide is 4.7922 g, and potassium doping is not performed.
[0051] 1. Example 2 Preparation of Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 The XRD pattern of Figure 1 As shown by Figure 1 It can be seen that the 2θ angles of 14.9°, 18.3°, 23.7°, 26.0°, 30.2°, 35.0°, 43.3°, 50.0°, 53.7°, 57.2° and 69.2° correspond to Li 2 ZnTi 3 O 8 The (110), (111), (210), (211), (220), (310), (004), (421), (422), (115) and (404) planes of Li 2 ZnTi 3 O 8 The standard card (PDF#44-1037) is basically consistent with the standard card (PDF#44-1037). The 2θ angles at 28.3°, 31.5°, 33.9° and 35.78° correspond to the (111), (111), (002) and (102) crystal planes of zirconia, respectively, which are consistent with the monoclinic zirconia (m-ZrO 2 ) standard card (PDF#80-0966), indicating that the prepared material should be monoclinic zirconium oxide.
[0052] 2. Li prepared in Example 2 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 The HRTEM image is as follows Figure 2 As shown, it can be found that Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 The lattice fringes of the material are obvious, indicating that its crystallinity is good. The interplanar spacing of the selected area was calculated, and the interplanar spacing of the coating layer was 0.25 nm, which corresponds to the (102) crystal plane of monoclinic zirconia, which is consistent with the XRD results, indicating that Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 Preparation was successful.
[0053] 3. Li was prepared according to the preparation method of Example 2 2 ZnTi 3 O 8 , Li 2 ZnTi 3 O 8 And the Li prepared in Example 2 1.9 K 0.1 ZnTi 3 O 8 and Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 , Li prepared in Example 4 1.85 K 0.15 ZnTi 3 O 8 , Li prepared in Example 6 2 ZnTi 3 O 8 @ZrO 2 The cycle performance graph, rate performance graph and impedance graph at a current density of 200 mA / g are shown in Figure 2. Figure 3 , Figure 4 and Figure 5 As shown:
[0054] Depend on Figure 3 It can be seen that at 200 mA g -1 The cycle performance test was carried out at a current density of . In the second cycle, Li 1.9 K 0.1 ZnTi 3 O8 @ZrO 2 The specific capacity is 338.1 mAh g -1 After 100 cycles, the specific capacity is 361.5 mAh g -1 Compared with Li without potassium doping 2 ZnTi 3 O 8 @ZrO 2 The discharge capacity after 100 cycles is 240.4 mAh g -1 ;Li 1.85 K 0.15 ZnTi 3 O 8 The discharge capacity after 100 cycles is 268.33 mAh g -1 . From this point of view, Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 The cycle performance is the best.
[0055] Depend on Figure 4 It can be seen that Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 at 50 mA g -1 The specific capacity of the second cycle at a current density of 413.9 mAh g -1 , at 50 mA g -1 , 100 mA g -1 , 200 mA g -1 , 500 mA g -1 and 1000 mA g -1 The specific capacity after 10 cycles is 424.9 mAh g -1 、410.7 mAh g -1 、394.1 mAh g -1 、337.6 mAh g -1 and 270.6mAh g -1 Compared with Li without potassium doping 2 ZnTi 3 O 8 @ZrO 2 at 50 mA g -1 , 100 mA g -1 , 200 mA g -1 , 500 mAg -1 and 1000 mA g-1 The specific capacity after 10 cycles is 245.6 mAh g -1 、239.7 mAh g -1 , 226.3 mAh g -1 , 207.8 mAh g -1 and 189.4 mAh g -1 ;Li 1.85 K 0.15 ZnTi 3 O 8 at 50 mA g -1 , 100 mA g -1 , 200 mA g -1 , 500mA g -1 and 1000 mA g -1 The specific capacity after 10 cycles is 308.05 mAh g -1 、281.77 mAh g -1 , 258.51mAh g -1 , 233.8 mAh g -1 and 207.27 mAh g -1 . From this point of view, Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 The rate performance is the best.
[0056] Depend on Figure 5 It can be seen that for Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 The AC impedance test was carried out, and after fitting, the charge transfer resistance was 68.51 Ω. Compared with Example 6 without potassium doping, Li 2 ZnTi 3 O 8 @ZrO 2 The charge transfer resistance is 242.1Ω. Compared with Example 4 with different doping ratios, Li 1.85 K 0.15 ZnTi 3 O 8 The charge transfer resistance is 460.5Ω, which shows that potassium doping and zirconium oxide coating modification can effectively reduce resistance and enhance conductivity.
[0057] 4. Li was prepared according to the preparation method of Example 2 2 ZnTi 3 O 8, Li 2 ZnTi 3 O 8 And the Li prepared in Example 2 1.9 K 0.1 ZnTi 3 O 8 and Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 0.1 mV s between 0.05-3 V -1 The cyclic voltammetry test was carried out at a scan rate of 1.38°, and the redox potential differences were 195 mV, 143 mV, and 114 mV, respectively. It can be seen that: Li 1.9 K 0.1 ZnTi 3 O 8 @ZrO 2 The redox potential difference is the smallest and the polarization is the smallest.
[0058] Finally, it should be noted that the above embodiments of the present invention are only examples for illustrating the present invention, and are not intended to limit the implementation methods of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all implementation methods here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing a zirconium oxide-coated potassium-doped lithium zinc titanate negative electrode material, characterized in that: The general chemical formula of the zirconium oxide coated potassium doped lithium zinc titanate negative electrode material is: Li x K y ZnTi3O8@ZrO2, wherein x+y=2, 0<y<0.2, and preparation method thereof The following steps are involved: S1: weigh anhydrous lithium acetate, zinc acetate dihydrate, nano titanium dioxide and potassium chloride according to the stoichiometric ratio, and then dissolve them in anhydrous ethanol and mix them evenly to obtain a mixed solution A for standby use; S2: Heat and stir the mixed solution A, then dry and sinter to obtain Li x K y ZnTi3O8 powder; S3: Li x K y Dissolve ZnTi3O8 powder in deionized water and mix well to obtain mixed solution B for later use; S4: preparing a solution of zirconium acetate and citric acid, and then adding the solution dropwise to the mixed solution B and stirring evenly to obtain a mixed solution C for later use; S5: The mixed solution C is placed in a sealed container and the solvent is evaporated to obtain a white gel-like substance, and then the white gel-like substance is dried at 75-85° C. for 24-36 hours, and then placed in a muffle furnace and sintered at 400-450° C. for 5-6 hours to obtain the Li x K y ZnTi3O8@ZrO2, where ZrO2 is monoclinic.
2. The method for preparing a zirconium oxide-coated potassium-doped lithium zinc titanate negative electrode material according to claim 1, characterized in that: Said y=0.
1.
3. The method for preparing a zirconium oxide-coated potassium-doped lithium zinc titanate negative electrode material according to claim 1, characterized in that: In step S1, anhydrous lithium acetate, zinc acetate dihydrate and potassium chloride are first dissolved in anhydrous ethanol, ultrasonicated for 30 to 40 minutes, and then nano titanium dioxide is added and ultrasonicated for 30 to 40 minutes to obtain a mixed solution A.
4. The method for preparing a zirconium oxide-coated potassium-doped lithium zinc titanate negative electrode material according to claim 1, characterized in that: In step S2, the mixed solution A is heated and stirred at a temperature of 75 to 85° C., and a gel-like substance is obtained after the solvent is volatilized.
5. The method for preparing a zirconium oxide-coated potassium-doped lithium zinc titanate negative electrode material according to claim 4, characterized in that: The gel-like substance obtained in step S2 is placed in an oven at 75-85°C and dried to obtain a white powder. The white powder is then placed in a microwave sintering furnace and sintered at 700-750°C for 15-20 minutes under an argon atmosphere to obtain Li x K y ZnTi3O8 powder.
6. The method for preparing a zirconium oxide-coated potassium-doped lithium zinc titanate negative electrode material according to claim 1, characterized in that: The molar ratio of zirconium acetate to citric acid is 1:
1.
7. The method for preparing a zirconium oxide-coated potassium-doped lithium zinc titanate negative electrode material according to claim 1, characterized in that: In step S3, Li x K y The mass volume ratio of ZnTi3O8 powder and deionized water is 3-8 g: 200-250 mL; in step S4, the mass of zirconium acetate is Li x K y 1-5% of the mass of ZnTi3O8 powder.
8. The method for preparing a zirconium oxide-coated potassium-doped lithium zinc titanate negative electrode material according to claim 1, characterized in that: In step S5, the mixed solution C is placed in a sealed container and reacted at 75-80° C. for 2-3 hours to obtain a white gel-like substance.
9. A zirconium oxide-coated potassium-doped lithium zinc titanate negative electrode material, characterized in that: The preparation method is described in any one of claims 1 to 8.
